Respon Pertumbuhan Dan hasil Tanaman Kacang Tanah (Arachis hypogaea L) yang di beri pupuk urea dan abu janjang kelapa sawit - Arief Kurniawan, Muhammad; Afrida, Elli (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
Peanuts (Arachis hypogaea L.) are important food crops that require essential nutrients such as nitrogen (N) and potassium (K) for optimal growth. Efficient fertilization is the key to increasing yields, especially in marginal areas. This study aims to determine the effect of urea fertilizer and oil palm ash on the growth and yield of peanuts. The research was carried out at the Experimental Garden of the Faculty of Agriculture, University of Medan Area using a factorial Group Random Design (RAK) with two factors: the dose of urea (0, 200, 250, 300 kg/ha) and oil palm ash (0, 15, 20, 25 tons/ha), each repeated three times. The parameters observed included plant height, flowering start day, number and weight of pods. The results showed that the application of oil palm ash had a significant effect on plant height, number of pods, and pod weight per sample, with the best treatment at a dose of 25 tons/ha. In contrast, urea fertilizers did not show a significant influence on all parameters. These results indicate that oil palm ash can be an effective and environmentally friendly alternative to organic fertilizers to increase peanut productivity.This study aims to determine the growth response and yield of peanut plants given urea fertilizer and oil palm bunch ash. This study was conducted using a factorial experimental design consisting of two factors, namely urea fertilizer and oil palm bunch ash. The results showed that the administration of urea fertilizer and oil palm bunch ash can increase the growth and yield of peanut plants. The administration of 200 kg/ha of urea fertilizer and 10 tons/ha of oil palm bunch ash can increase the yield of peanut plants by 35.6% compared to the control. Therefore, the administration of urea fertilizer and oil palm bunch ash can be an alternative to increase the growth and yield of peanut plants.